Antipsychotic Use With and Without Comorbid Psychiatric Diagnosis Among Adults with Intellectual and Developmental Disabilities. (June 2018) - Lunsky, Yona; Khuu, Wayne; Tadrous, Mina; Vigod, Simone; Cobigo, Virginie; Gomes, Tara
Objective: Antipsychotic use is controversial in the management of adults with intellectual and developmental disabilities (IDD) because of inconclusive evidence for efficacy in the absence of a comorbid psychiatric condition, and substantial concerns about adverse effects. We aimed to characterize antipsychotic use among Ontario adults with IDD and compare profiles of those with and without a documented psychiatric diagnosis. Method: This population-based study included 51, 881 adults with IDD under 65 y as of April 2010 receiving provincial drug benefits in Ontario who were followed until March 2016 to identify those dispensed at least one antipsychotic medication. Profiles of those with and without a psychiatric diagnosis were compared. Results: Overall, 39.2% of adults ( n = 20, 316) were dispensed an antipsychotic medication, which increased to 56.4% in a subcohort residing in group homes. Almost one-third (28.91%) of people prescribed an antipsychotic medication did not have a documented psychiatric diagnosis. Those without a psychiatric diagnosis differed considerably from those with a diagnosis. In particular, those without a psychiatric diagnosis were older, less likely to have used antidepressants or benzodiazepines in the year before, and less likely to have used ambulatory and acute care. Conclusions: Antipsychotic use in IDD is common, and occurs frequently without a psychiatric diagnosis. Attention toward how antipsychotics are prescribed and monitored for people with IDD in Canada is warranted to ensure appropriate prescribing.